(untitled) (Cambridge, 2002)
Part of a three-volume set on business strategy, performance, and competencies for manufacturers, this text presents an approach to reviewing current practices and developing long- term strategic plans. Coverage includes, for example, identifying customer product groups, defining business objectives, assessing current strategy, and embedding strategy making into the business culture.
Keywords: Industrial management,Strategic planning,Quản lý công nghiệp,Quy hoạch lâu dài